Potensi Sprayer Otomatis sebagai Solusi Masalah Penyiraman Tanaman untuk Petani Cabe - Finahari, Nurida; Budi, Khanif Prasetyo; Putra, Toni Dwi (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2019)
Chili (capsium annum L) is an important horticulture commodity. The availability of water is one of the supporting factors for the chili crop production system. Meeting the water needs of chili greatly affects its growth. One obstacle for farmers is managing time when processing land. Farmers spend a lot of time watering and fertilizing plants. This has an impact on the time efficiency of farmers to cultivate other land and clear weeds. The design development of a plant irrigation system using soil moisture sensors can be an alternative solution. This system is capable of automatically watering and detecting the availability of water for watering. The control system used is Arduino Uno as the main controller. From the automated design mindset, it can be said that it is possible to carry out an automation process on the work of watering chili plants. The problem of adequate water in the dry season can be overcome based on controlling the amount of water spray, which is adjusted to the soil moisture sensor readings. As for other problems that need to be studied, related to the system of controlling soil moisture during the rainy season. This problem can be assessed by reference to a soil moisture based watering control system that might also be combined with a soil dryer / dryer system. This can be developed into the next appropriate technology as a community service work.